Anthroponyms of Jewish Women in the 16th Century Grand Duchy of Lithuania - Čirūnaitė, Jūratė (Respectus Philologicus, 2012)
The most popular names among Jewish women in 16th century Lithuania were Simcha, Marjam, Anna, Debora. The names were most frequently recorded as diminutives (63.3%), with only 36.4% appearing in canonical forms. The smallest group comprises names formed using only anthroponyms that were derived from those of (male) family members (29.6%). 35.2% of the namings are recorded as mixed type. The same number of women are recorded using only names in the documents.Personal names are included in 70.4% of recorded women’s namings. Andronyms (anthroponyms formed from the spouse’s name) were found in 64.8% of all the records. 9.3% of women’s namings include anthroponyms formed using the spouse’s patronymic. Only 1.9% of namings had a female patronymic (the derivative of the suffix -owna/-ewna).One-member female namings prevail (59.3%). Two-member namings comprise 33.3%. Three members are found in 5.6% of the namings, while four-membered ones comprise 1.9%. The average length of the namings is 1.5 times that of the anthroponyms.Common words explaining anthroponyms were found in 68.5% of the namings. Common words related to religion prevail (51.4%). 29.7% of the common words characterize relationships or family status, and only 10.8% describe occupation, post or trade (vocation). Common words describing descent (social origin) comprise only 8.1% of all the women’s namings.Namings consisting only of anthroponyms of family members can be subdivided into the following subgroups: 1) derivatives of the suffix -owaja/-ewaja; 2) derivatives of the suffix ‑owaja/-ewaja; 3) derivatives of the suffix -owaja/-ewaja + the genitive of a male patronymic; 4) derivatives of the suffix -owaja/-ewaja + a male patronymic + the genitive of a male patronymic. Namings without anthroponyms consisting of family members included names and names with common words. Mixed namings consisted of: 1) a name + a derivative of the suffix -owaja/-ewaja; 2) a derivative of the suffix -owaja/-ewaja + the genitive of a male patronymic + a name; 3) a derivative of the suffix -owaja/-ewaja + the genitive of a male patronymic + a name + a female patronymic.The most popular type of naming is a recorded name.
Keywords: onomastics; name; patronymic